Influence of Zr Content in Ti-40Nb-xZr Alloys on the Microstruture, Elastic Modulus and Microhardness - Rafael Formenton Macedo dos Santos; Carolina Neves Reis; Conrado Ramos Moreira Afonso (Materials Research, 2023)
In recent years, there has been a growing interest in the search for metallic alloys with favorable mechanical and chemical characteristics that elicit a positive biological response. Among these alloys, β-Ti alloys have attracted significant attention due to their low elastic modulus and excellent biocompatibility. The addition of Nb contributes to stabilizing the β phase at room temperatures, leading to the transformation of β into β + α (β-isomorph). Additionally, despite Zr being commonly considered a neutral element, it can exhibit a β-stabilizing characteristic when combined with betagenic elements. Both Nb and Zr have been shown to effectively increase the lattice parameter of the β phase, which is advantageous for reducing the elastic modulus. The primary objective of this study was to characterize β-Ti alloys within the Ti-Nb-Zr system, specifically Ti-40Nb-20Zr, Ti-40Nb-30Zr, and Ti-40Nb-40Zr (wt.%) produced via arc furnace casting. The study aimed to investigate the influence of the proportion of β-stabilizing or betagenic elements on the microstructure and properties of the alloys, including Vickers microhardness and elastic modulus.